SYNTHESIS, CHARACTERIZATION AND APPLICATION OF A FERROCENYL AZO-BASED LIGAND AS AG+- DETECTOR IN AN AQUEOUS SYSTEM - Adesoji, Adedoyin Oluseyi; Shotonwa, Ibukun Oluwaseun (FUDMA JOURNAL OF SCIENCES, 2024)
Over the years, humans and the environment have been exposed to various toxic ionic species that emanated, majorly, from anthropogenic sources. In this study, a new ferrocenyl-azo based chemosensor, ferrocenyl 1-(2-phenylazo)-2-naphtholate (FPN) for the determination of silver ions was developed via catalytic reduction and diazotization routes. The structural features were confirmed by spectroscopic methods involving proton NMR, GC/MS and FTIR. Having exposed the product to different metal solutions, Ag+ was distinctively recognized, revealing FPN as an effective and sensitive chemosensor. The binding behavior of FPN towards the sensitive silver ion was investigated using Job’s plot, and a metal:ligand ratio of 1:1 was revealed. The study showed a bathochromic shift and a new peak band was observed at 275 nm in the absorption spectra of FPN. The absorption experiments demonstrate that FPN as a rapid and reliable sensor capable of determining silver and ferric ions. Therefore, ferrocenyl 1-(2-phenylazo)-2-naphtholate ligand is highly recommended as an alternative route in detecting silver ions in both organic and aqueous media.